2015
DOI: 10.1186/s12931-015-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of budesonide/formoterol combination and fluticasone/salmeterol combination among chronic obstructive pulmonary disease patients new to controller treatment: a US administrative claims database study

Abstract: BackgroundInhaled corticosteroid/long-acting β2-agonist combinations (ICS/LABA) have emerged as first line therapies for chronic obstructive pulmonary disease (COPD) patients with exacerbation history. No randomized clinical trial has compared exacerbation rates among COPD patients receiving budesonide/formoterol combination (BFC) and fluticasone/salmeterol combination (FSC) to date, and only limited comparative data are available. This study compared the real-world effectiveness of approved BFC and FSC treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
5
22
1
Order By: Relevance
“…A Canadian study19 also found that the risk of exacerbations requiring emergency department visits (adjusted relative risk [RR] =0.75; 95% CI: 0.58–0.97), hospitalizations (adjusted RR =0.61; 95% CI: 0.47–0.81) for COPD and anticholinergic medication use (adjusted RR =0.71; 95% CI: 0.57–0.89) was lower with fixed-dose budesonide/formoterol than with fixed-dose fluticasone/salmeterol during 1 year of analysis. In contrast to our study, the administrative claims database study conducted by Kern et al20 in the US found similar rates of utilization of health care resources and rates of exacerbations (rate ratio =1.02; 95% CI: [0.96–1.09], P =0.56) between patients initiating budesonide/formoterol or fluticasone/salmeterol during the first year of starting therapy. Since, there is no generally agreed definition for an exacerbation of COPD, because exacerbations have a variety of causes and severities, the direct comparison between studies is difficult 21.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A Canadian study19 also found that the risk of exacerbations requiring emergency department visits (adjusted relative risk [RR] =0.75; 95% CI: 0.58–0.97), hospitalizations (adjusted RR =0.61; 95% CI: 0.47–0.81) for COPD and anticholinergic medication use (adjusted RR =0.71; 95% CI: 0.57–0.89) was lower with fixed-dose budesonide/formoterol than with fixed-dose fluticasone/salmeterol during 1 year of analysis. In contrast to our study, the administrative claims database study conducted by Kern et al20 in the US found similar rates of utilization of health care resources and rates of exacerbations (rate ratio =1.02; 95% CI: [0.96–1.09], P =0.56) between patients initiating budesonide/formoterol or fluticasone/salmeterol during the first year of starting therapy. Since, there is no generally agreed definition for an exacerbation of COPD, because exacerbations have a variety of causes and severities, the direct comparison between studies is difficult 21.…”
Section: Discussioncontrasting
confidence: 99%
“…Both budesonide/formoterol and fluticasone/salmeterol demonstrated reduction in the overall rate of exacerbations, although published studies13,20 suggest differences in the exacerbation rates between the two ICS/LABA combinations (budesonide/formoterol and fluticasone/salmeterol). A matched-cohort, register-linkage study13 in Sweden reported that long-term treatment with a fixed combination of budesonide/formoterol was associated with a significant lower health care consumption-defined exacerbations than fluticasone/salmeterol in patients with COPD (difference of 26.6%; P <0.0001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The inclusion criteria differed from PATHOS in that patients who were not currently being treated with ICS were also included in the analysis, and in the follow-up period was shorter (1 versus 2 years) [Kern et al 2015].…”
mentioning
confidence: 99%
“…As a result, more recent guidance suggests that combination LABA/ICS should only principally be prescribed in COPD patients with asthma-like symptoms with exacerbations in view of potential adverse effects [12,21]. It can be difficult though to assess differences in outcomes between the different combination formulations and inhaler types [28][29][30][31][32]; consequently, the choice of inhaler device and ease of use do play an appreciable role in the choice of device prescribed with poor inhaler technique known to compromise care [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%